Libo Plant Potential (Ficus Variegata, Blume) as Source of Potential Pharmaceutical Materials - Byungsik Lee (International Journal of Science and Society, 2020)
Libo (Ficus varieagata) is a wild plant that has not been utilized in any form, including traditional because it has latex plant fruit and bark, and if the latex on the skin causes itching to occur even irritation. The nature of that causes undesirable fruit so that the fruit-eating animals are well maintained. Libo ripe fruit on the tree will fall to the ground and grow into a mature Libo tree. Potential plant fruiting and fruit continuously disliked fruit-bearing animals that populations of plants Libo maintained and continued to grow. Has conducted numerous studies on fruit Libo relations with pharmaceutical potential and proven potential as a source of antioxidants, cytotoxic or anticancer, larval exterminator A. Aegypti, and as an antibacterial. These potentials can be used as a preservative, an anticancer drug, and a source of antibiotics if the research is done in detail. Libo fruit also contains a group of secondary metabolites that are highly variable so it still allows for other uses in the pharmaceutical field.